HIV retesting in pregnant women in South Africa: Outcomes of a quality improvement project targeting health systems’ weaknesses - Lauren M. Golden (Southern African Journal of HIV Medicine, 2018)
Introduction: South Africa is moving towards achieving elimination of mother-to-child transmission (eMTCT) but gaps remain in eMTCT programmes. Documenting successful outcomes of health systems interventions to address these gaps could encourage similar initiatives in the future.